Determinación de las competencias organizacionales de las mipymes agroproductivas avícolas de la zona norte de Manabí - Murillo Cedeño, Silvia Patricia (2019)
The main objective of this work was to determine the organizational competencies of the small and medium-sized agro-productive poultry companies in the northern area of Manabí for the contribution to the management of the recruitment and selection of human talent. For this purpose, an investigation with qualitative-quantitative approach was developed, since the qualities of the object of investigation were extracted and then transformed to values by means of the respective non-experimental treatment; in addition, the bibliography was applied which allowed to collect information from the different texts related to the work; field, since they went to the facts places to collect data from primary sources. The general methods were the inductive, deductive, descriptive, and as specific methods the Delphi, for the selection of organizational competencies the Estanino method for processing the surveys was applied to employees which allowed to transform the data to manageable information and reliable results. In the same way, techniques and tools were applied that made operational methods such as: interview, survey, characterization sheet and SPSS, VISIO computer systems. As a result, the organizational competencies for Poultry in the northern area of Manabí were: Results orientation, Work quality, Commitment, Ethics, Perseverance, Customer Orientation, Innovation, Empowerment and Integrity. For the development of the research, the MARCOS VIVANCO and AVIBURZ poultry companies were selected, which are finally prepared with the Competency Manual that contributes to an efficient and effective recruitment and selection process.